STRENGTHENING THE IMPLEMENTATION OF SCHOOL-BASED MANAGEMENT THROUGH HUMAN RESOURCE COMPETENCY DEVELOPMENT - Syamsul Arifin; Anis Zohriah (LP2M IAI Al-Khairat Pamekasan, 2026)
School-based management (SBM) is one form of implementation of educational decentralization policy that aims to improve the effectiveness of education management and the quality of learning at the educational unit level. This study aims to analyze the concepts, principles, quality indicators, and implementation of SBM in improving the quality of education. The study uses a qualitative approach with a library research method. Data were obtained from various scientific literature sources in the form of books, academic journals, and educational policy documents relevant to the topic of educational decentralization and education management. Data were analyzed using content analysis techniques to identify key concepts, compare previous research findings, and compile a conceptual synthesis regarding SBM implementation. The results of the study indicate that the implementation of SBM has the potential to improve the quality of education by strengthening school independence, more flexible resource management, and increasing stakeholder participation in educational decision-making. However, the effectiveness of SBM implementation is still influenced by the quality of principal leadership, managerial capacity, school organizational culture, and community support. In addition, resource inequality and low understanding of the SBM concept also become obstacles in its implementation. Therefore, strengthening the implementation of MBS needs to be directed at improving human resource competency, strengthening transparent and accountable school governance, and developing a continuous monitoring and evaluation system to achieve systematic and sustainable improvements in education quality. Keywords: School-Based Management, Educational.